Staff training and development in information sciences (Anmol Pubications, 2001)
Contents of material: 1/ Library training. 2/ Library leadership. 3/ Staff training. 4/ Job satisfaction. 5/ Staff organication. 6/ Staff supervision. 7/ Effective librarianship.